The role of microRNA-4723-5p regulated by c-myc in triple-negative breast cancer. Issue 4 (1st April 2022) - Jin, Xi-Xin; Gao, Chao; Wei, Wen-Xin; Jiao, Chong; Li, Li; Ma, Bin-Lin; Dong, Chao
ABSTRACT: The aim of this study was to investigate the expression of miRNA regulated by c-myc and its mechanism in three negative breast cancer (TNBC). We constructed MDA-MB-231 cell line with low expression of c-myc by lentivirus short hairpin RNA (shRNA), analyzed the miRNA expression profile of MDA-MB-231 cell line with different expression levels of c-myc by high-throughput sequencing technology, obtained differential miRNA by bioinformatics analysis and statistical analysis, and verified hsa-mir-4723-5p by Quantitative Real-time polymerase chain reaction(QRT-PCR). The target gene of hsa-mir-4723-5p was analyzed by miRDB and miRWalk database. The results showed that there were significant differences in 126 miRNAs in c-myc knockdown cell lines compared with the control group, of which 84 were significantly up-regulated and 42 were significantly down regulated. According to the results of miRNA sequencing, the miRNA closely related to the expression of c-myc was hsa-mir-4723-5p. QRT PCR showed that the expression of hsa-mir-4723-5p was down regulated in TNBC cell line MDA-MB-231 with low expression of c-myc, which was positively correlated with the expression. The target genes of hsa-mir-4723-5p were predicted according to mirdb and mirwalk database. A total of 112 target genes were obtained, and 107 target genes were related to hsa-mir-4723-5p. Through mirdb and mirwalk databases, it was found that the target gene TRAF4 of hsa-mir-4723-5p may be related to cancer pathway and affect tumor metastasis. In conclusion, the hsa-miR-4723-5p regulated by c-myc may be involved. Abstract : uf0001